An investigation into the possible causes of decline in the Acacia Erioloba population of the Kathu area - Van der Merwe, Karien (University of the Free State, 2001)
Concerned residents have been reporting a decline in the A. erioloba population of the Kathu area to the Northern Cape Nature Conservation Service (NCNCS) since the early 1980's. This is the third study on this subject initiated by the NCNCS, and aims to elucidate the possible causes of decline in the A. erioloba population of the Kathu area. Five investigation sites were identified: the Khai-Apple Nature Reserve (KANR); the farms Lylyveld and Dernaneng, both situated down-wind with regard to the Sishen lscor Iron Ore Mine (SllOM); the Sishen Golf Course; and the farms Swarthaak and Knapdaar, both situated upwind with regard to the SllOM. The Sandveld Nature Reserve on the Free State side of the Bloemhof Dam, served as control site. In order to identify potential problem areas regarding the A. erioloba population of the Kathu area, the A. erioloba population structure of the study and control areas were compared. Irregularities in the structure of the study area indicated that some factor(s) is either a) preventing individuals from reaching middle height classes, or b) kill ing trees in these classes. To eliminate one of these options, another structure study was conducted, comprising dead individuals only. Results indicated that both factors (a+ b) play a role. By means of questionnares that were distributed th roughout the region, three major factors, potentially harmful to the A. eriofoba population, were identified. They are the mining activities of the SllOM, management strategies and natural phenomena. Two aspects of the SllOM were postulated to be potentially harmful to the A. erioloba population: the mine dust formed as a by-product of mining activities; and the lowering of ground water levels. Scanning electron microscopy confirmed that A. erioloba leaves are indeed damaged by mine dust. Through further investigations the effect of mine dust on the transpiration rate, chlorophyll a and b content and protein content of A. erioloba leaves were determined. The results of this study indicated that mine dust has no marked effect on any ofthese variables. The effect of mine dust on the germination of A. erioloba seeds and the growth potential of its embryos were also determined. No inhibitive effect was detected on either of these processes - in fact, mine dust seemed to stimulate both. No trials regarding the effect of the lowering of ground water levels by the SllOM on A. erioloba were conducted, due to its impracticality. Instead, with the aid and insight of geohydrologists it was concluded that the lowering of ground water levels does not affect A. erioloba. The aquifer underneath the mining area is seperated from the other two aquifers in the area (situated under Kathu and the KANR) by a dolorite dyke, which is impermeable to water. This was confirmed in the present study by comparing the water pumping rates of the SllOM to bore hole levels throughout the region. Three management strategies applied in the Kathu area were identified as being potentially harmful to A. erioloba: the overstocking of browsers and mixed feeders in the KANR; pod removal; and the uninformed use of chemicals. The current stocking rate of the KANR compared to its current browsing capacity, revealed that the reserve is grossly overstocked. This results in the suboptimal regeneration of A. erioloba, as seedlings cannot reach the stage where browsing doen not prove to be fatal anymore. Pod removal also inhibits optimal reg eneration, as no A. erioloba soil seed bank was found. This implies that no genetic variation in the A. erioloba pululation is built up over time, which may prove to be fatal in the event of future changes in environmental conditions. The uninformed use of non-specific chemicals in an attempt to eradicate A. mellifera on farms is furthermore also eradicating A. erioloba. One natural phenomenon was hypothesised to be inhibiting to the regeneration of A. erioloba, namely seed predation by Bruchidae. Germination trials revealed that bruchid seed predation inhibits the regeneration of A. erioloba. It is, however, compensated for by producing a relatively large seed yield per tree in an attempt to over-saturate predators. Management recommendations on the effective management of A. erioloba in the Kathu area were made. Recommendations included correct stocking rates, increasing community involvement in conservation, veld monitoring and the correct use of chemicals

Besorgde inwoners van Kathu rapporteer reeds sedert die vroeë 1980's 'n afname in die grootte van die A. erioloba populasie van die gebied aan die Noord-Kaap Natuurbewaringsdiens. Hierdie is die derde studie rakende die aangeleentheid wat deur die Noord-Kaap Natuurbewaringsdiens geïnisieer is, en het die doel om moontlike oorsake van die afname in die populasiegrootte van die A. erioloba in die Kathu distrik te identifiseer en aan te spreek. Vyf ondersoek-areas is geïdentifiseer, naamlik die Khai-Appel Natuurreservaat (KAN); die plase, Lylyveld en Demaneng, wat albei wind-af van die Sishen Yskor Ysterertsmyn (SYY) gelee is; die Sishen Gholfbaan; en die plase, Swarthaak en Knapdak, wat albei wind-op van die SYY geleë is. Die Sandveld Natuurreservaat aan die Vrystaatkant van die Bloemhofdam is as kontrolegebied geïdentifiseer. Met die doel om verdere ondersoeke te rig, is die A. erioloba populasiestruktuur van die studieen kontrolegebiede vergelyk. Onreëlmatighede in die struktuur van die studiegebied het aangedui dat daar wel faktore teenwoordig is wat a) saailinge verhoed om hoër hoogteklasse te bereik, of b) wat bome in die middel-hoogteklasse doodmaak. 'n Struktuuropname waarin net dooie A. erioloba individue aangeteken is, is dus gedoen om een van bogenoemde moontlikhede te elimineer. Resultate het getoon dat albei hierdie moontlikhede (a + b) in Kathu 'n rol speel. Deur middel van vraelyste wat deur die distrik versprei is, is drie hoofareas wat moontlik skadelik vir A. erioloba kan wees, geëdentifiseer, naamlik die mynbou aktiwiteite van die SYY, bestuurspraktyke, en natuurlike verskynsels. Twee aspekte van die SYY is geïdentifiseer as potensieel skadelik vir die A. erioloba populasie, naamlik die mynstof wat gevorm word as 'n byproduk van mynbou-aktiwiteite, en die verlaging van grondwatervlakke. Skandeer-elektron-mikroskopie het getoon dat blare wel deur mynstof beskadig word . Die invloed van mynstof op die transpirasietempo, chlorofil a en b inhoud en proteïeninhoud van A. erioloba blare is bepaal. Daar is gevind dat mynstof geen noemenswaardige invloed op enige van hierdie veranderlikes het nie. Sowel die invloed van mynstof op ontkieming, as die groeipotensiaal van die embrio is bepaal deur middel van ontkiemingsproewe. Geen inhiberende invloed is op laasgenoemde prosesse waargeneem nie; inteendeel, dit blyk dat mynstof albei stimuleer. Geen studies is onderneem aangaande die invloed van 'n verlaging in grondwatervlakke op A. erioloba nie, weens die onuitvoerbaarheid van sulke proewe. Navraag aangaande die kwessie is wel gedoen by verskeie geohidroloë. Die volgende afleiding is gemaak: weens die teenwoordigheid van 'n ondeurdringbare dolerietgang tussen die mynakwifer en die ander twee akwifers van die gebied, het die verlaging van grondwatervlakke in die myngebied geen invloed op die borne van Kathu nie. Hierdie stelling is bevestig deur die waterpompsyfers van die verskillende mynkompartemente met die van boorgatwatervlakke regdeur die streek te vergelyk. Drie bestuurspraktyke is geïdentifiseer as potensieel skadelik vir A. erioloba, naamlik die oorbelading van blaar- en gemengde vreters; peulverwydering; en die onoordeelkundige gebruik van chemikalieë. 'n Vergelyking tussen die huidige belading van die KAN en die huidige blaarvreterkapasiteit van die gebied het aan die lig gebring dat hierdie area totaal oorbelaai is. Dit het tot gevolg dat A. erioloba saailinge nie 'n kans gegun word om hoogteklasse te bereik waar benutting nie meer fataal is nie. Peulversameling beperk voortplanting deurdat daar geen saadbank opgebou word nie. Dit impliseer dat geen genetiese variasie in die A. erioloba populasie oor tyd opgebou word nie, wat fataal kan wees indien omgewingstoestande in die toekoms sou verander. Die onoordeelkundige gebruik van chemikalieë in 'n paging om A. mellifera, wat as indringer in hierdie gebied beskou word, uit te roei , doen tans groot skade aan die A. erioloba populasie.Een natuurlike verskynsel wat as potensieel skadelik vir A. erioloba bestempel is, is ondersoek, naamlik saadpredatering deur Bruchidae kewers. Ontkiemingsproewe het aan die lig gebring dat saadpredasie wel die voortplanting van A. erioloba inhibeer. Daar word egter hiervoor gekompenseer deurdat elke volwasse A. erioloba individu 'n groot aantal sade produseer. In die proses word oorvoorsien in saadpredatore se behoeftes en het saadpredasie nie 'n negatiewe impak op die A. erioloba populasie nie. Aanbevelings is gemaak aangaande die effektiewe bestuur van A. erioloba in die Kathu omgewing, insluitend die korrekte belading van wild, grater gemeenskapsbetrokkenheid in bewaring, veldmonitering en die korrekte gebruik van chemikalieë.
Dissertation (M.Sc. (Botany and Genetics))--University of the Free State, 2001
Keywords: Decline; Kathu; Mine dust; Water levels; Browse pressure; Chemicals; Pod removal; Bruchid beetle predation; Tree declines -- South Africa -- Kathu; Conservation biology; Acacia -- South Africa -- Kathu; Acacia erioloba